Math, asked by susil39, 1 year ago


4.
Prove that:
give answer please​

Attachments:

Answers

Answered by pratyush4211
5

( \frac{ {2}^{ \frac{1}{3} } }{ {2}^{ \frac{ - 1}{3} } } ) {}^{3}  +  \frac{ {3}^{ \frac{1}{2} } }{ {3}^{ \frac{ - 1}{2} } }  = 7

According to Law of Exponent

 \frac{ {x}^{a} }{ {x}^{b} }  =  {x}^{a - b}

Now

( {2}^{ \frac{1}{3} - ( -  \frac{1}{3} )} ) {}^{3}  + ( {3}^{ \frac{1}{2}  - (  - \frac{ 1}{2}) }) \\  \\  ({2}^{ \frac{1}{3}  +  \frac{1}{3} }  ) {}^{3}  + ( {3}^{ \frac{1}{2}  +  \frac{1}{2} } ) \\  \\ ( {2}^{ \frac{2}{3} } ) {}^{3}  +  {3}^{ \frac{2}{2} }  \\  \\  {2}^{ \frac{2}{3} \times 3 }  + 3 \\  \\  {2}^{2}  + 3 \\  \\ 4 + 3 \\  \\  = 7

LHS=7

RHS=7

Hence,

LHS=RHS. (proved)

Answered by ap5495989
0

Answer:

hiiiiiiiii..............

Similar questions